2020
DOI: 10.7150/thno.46566
|View full text |Cite
|
Sign up to set email alerts
|

TFE3, a potential therapeutic target for Spinal Cord Injury via augmenting autophagy flux and alleviating ER stress

Abstract: Background and Aim: Increasing evidence suggests that spinal cord injury (SCI)-induced defects in autophagic flux may contribute to an impaired ability for neurological repair following injury. Transcription factor E3 (TFE3) plays a crucial role in oxidative metabolism, lysosomal homeostasis, and autophagy induction. Here, we investigated the role of TFE3 in modulating autophagy following SCI and explored its impact on neurological recovery. Methods: Histological analysis via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 66 publications
2
73
1
Order By: Relevance
“…It is well-known that, following an HI insult, mitochondrial dysfunction results in the production of excess ROS, which rapidly overwhelms neuronal antioxidant capacity 16 . The high levels of ROS induce oxidative damage to cellular macromolecules, which initiates a cycle of ROS production and organelle dysregulation that eventually triggers neuronal apoptosis 1 , 16 , 104 - 107 . We found that prenatal PBM treatment significantly alleviated HI-induced oxidative damage to lipids, proteins, and DNA.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that, following an HI insult, mitochondrial dysfunction results in the production of excess ROS, which rapidly overwhelms neuronal antioxidant capacity 16 . The high levels of ROS induce oxidative damage to cellular macromolecules, which initiates a cycle of ROS production and organelle dysregulation that eventually triggers neuronal apoptosis 1 , 16 , 104 - 107 . We found that prenatal PBM treatment significantly alleviated HI-induced oxidative damage to lipids, proteins, and DNA.…”
Section: Discussionmentioning
confidence: 99%
“…We followed the methods of our previous research (Zhou et al, 2020). TFE3-KI/wt mice were generated by the Nanjing Biomedical Research Institute of Nanjing University.…”
Section: Production Of Tfe3-ki/wt Micementioning
confidence: 99%
“…Enzyme-Linked Immunosorbent Assay (ELISA) was performed as previously described (Zhou et al, 2020). At a word, the flap tissue and cell supernatant were homogenized with PBS, and then, they were repeatedly frozen and thawed with liquid nitrogen.…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…Traumatic spinal cord injury (SCI) is a devastating condition that results in long-term disability and death worldwide [ 1 ]. Neuronal cell death is one of the most critical pathological issues caused by direct mechanical impact, followed by a series of secondary molecular cascades, including mitochondrial damage, reactive oxygen species (ROS) and misfolded protein accumulation, and the inflammatory response [ [2] , [3] , [4] ]. Although neural tissue is associated with limited intrinsic regenerative capability, increasing evidence indicates that targeting these secondary molecular processes is a therapeutic method for improving functional recovery after SCI in many animal cases [ [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%